Awareness of Sexual Partner’s HIV Status Among Men Who Have Sex With Men in China: Cross-Sec. tional Survey Study - Qian Ma; Tingting Jiang; Wanjun Chen; Shaoqiang Jiang; Jinlei Zheng; Hui Wang; Lin He (JMIR Public Health and Surveillance)
Abstract BackgroundMen who have sex with men (MSM) constitute a significant proportion of individuals living with human immunodeficiency virus. Over the past few years, China has implemented various strategies aimed at increasing the rate of HIV testing and reducing HIV transmission among MSM. Among these, the disclosure of HIV serostatus is an effective prevention strategy. ObjectiveThis study aimed to assess HIV serostatus disclosure and identify factors associated with awareness of sexual partners’ HIV status among MSM to provide a scientific basis for promoting HIV testing and reducing HIV transmission. MethodsA cross-sectional study based on a large-scale web-based survey was conducted among MSM in Zhejiang province, China, between July and December 2023. MSM who were HIV-negative or had an unknown HIV status were recruited from the Sunshine Test, a web-based platform that uses location-based services to provide HIV prevention services. Participants were required to complete a questionnaire on demographic characteristics, sexual behavior, rush popper use, awareness of sexual partners’ HIV status, and knowledge of pre-exposure prophylaxis (PrEP) and postexposure prophylaxis (PEP). A multinomial regression model was used to identify the factors associated with awareness of sexual partners’ HIV status. ResultsA total of 7629 MSM participated in the study, with 45.2% (n=3451) being aware, 35.4% (n=2701) being partially aware, and 19.4% (n=1477) being unaware of their sexual partner’s HIV status. The multinomial logistic regression analysis revealed the following results. Compared to those who were unaware of their sexual partner’s HIV status, participants who were students (adjusted odds ratio [aOR] 1.43, 95% CI 1.09‐1.86), had a monthly income of more than US $1400 (aOR 1.36, 95% CI 1.03‐1.80), had insertive anal sex (aOR 1.35, 95% CI 1.12‐1.63), had only male sexual partners (aOR 1.53, 95% CI 1.28‐1.82), had 1 sexual partner in the past 3 months (aOR 2.36, 95% CI 2.01‐2.77), had used condoms for the past 3 months (aOR 1.72, 95% CI 1.33‐2.22), had frequently used rush poppers in the past 3 months (aOR 2.27, 95% CI 1.81‐2.86), were aware of HIV PrEP (aOR 2.04, 95% CI 1.68‐2.48), were aware of HIV PEP (aOR 1.69, 95% CI 1.39‐2.06), used mail reagent self-testing (aOR 1.19, 95% CI 1.04‐1.36), and had previously undergone HIV testing (aOR 1.40, 95% CI 1.16‐1.69) were associated with increased odds of being aware of their sexual partner’s HIV status. ConclusionsOverall, 45.2% of MSM who were HIV-negative or had an unknown status were aware of their sexual partners’ HIV status in China. We suggest strengthening targeted interventions through web-based platforms and gay apps to promote the disclosure of HIV serostatus and reduce HIV transmission among MSM.